Role of a Pyroptosis-Related lncRNA Signature in Risk Stratification and Immunotherapy of Ovarian Cancer - Zhang, Zeyu; Xu, Zhijie; Yan, Yuanliang (Frontiers in Medicine, 2022)
Background: Pyroptosis is a newly recognized form of cell death. Emerging evidence has suggested the crucial role of long non-coding RNAs (lncRNAs) in the tumorigenesis and progression of ovarian cancer (OC). However, there is still a poor understanding of pyroptosis-related lncRNAs in OC. Methods: TCGA database was accessed for gene expression and clinical data of 377 OC patients. Two cohorts for training and validation were established by random allocation. Correlation analysis and Cox regression analysis were used for identifying pyroptosis-related lncRNAs and constructing a risk model. Results: 6 pyroptosis-related lncRNAs were included in the final signature with unfavorable survival data. The subsequent ROC curves showed promising predictive value of patient prognosis. Further multivariate regression analyses confirmed the signature as an independent risk factor in the training cohort (HR: 2.242, 95%CI: 1.598-3.145) and the validation cohort (HR: 1.884, 95%CI: 1.204-2.950). A signature-based nomogram was also established with a C-index of 0.684 (95%CI: 0.662-0.705). Involvement of the identified signature in multiple immune-related pathways was revealed by functional analyses. Moreover, the signature was also associated with a higher expression of three immune checkpoints (PD-1, B7-H3, and VSIR), suggesting the potential of the signature as an indicator for OC immunotherapies. Conclusion: This study suggests the identified pyroptosis-related lncRNA signature and the signature-based nomogram may serve as methods for risk stratification of OC. The signature is also associated with the tumor immune microenvironment, potentially providing an indicator for patient selection of immunotherapy in OC.